Improved droop control strategy for distributed photovoltaic power generation systems - Zhengwan, Deng; Ningyu, Gao; Yali, Zhu (Frontiers in Energy Research, 2024)
The control strategy of a distributed photovoltaic (PV) power generation system within a microgrid consists of an inner-loop controller and an outer-loop controller. The inner-loop controller is divided into two types, namely, the maximum power point tracking (MPPT) control strategy and DC bus voltage support strategy. Switching between these two control strategies results in issues such as DC bus overvoltage, system oscillations, or even PV system failure. An improved droop control strategy with a novel inner-loop controller is proposed, incorporating an output power derivative regulator. The control system unifies MPPT and DC bus voltage support strategy without switching the controller structure. A simulation model is built to validate the effectiveness of the proposed control strategy, and the results show that the ripple of DC bus voltage decreases by more than 60%.